Telaah Tematik Esensi Makna ‘Ismah dalam al-Qur’an - Suraya Attamimi; Aswadi Aswadi; Hammis Syafaq (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Thematic Study of the Essence of the Meaning of ‘Ismah in the Qur'anThis article discusses the interpretation of the term ‘is}mah in the Qur'an. As a word with conceptual implications, ‘is}mah is often used by Muslim scholars when discussing the incorruptible innocence of the prophets from sins (‘is}mat al-Anbiya>’). This article reviews the meaning of the word along with its scope to see the appropriateness of the theological connotations by collecting all Qur’anic verses that use the word ‘is}mah and its derivations. The twelve verses collected were then arranged chronologically according to the moments of their revelation and analyzed using a thematic interpretation method. The results of this study indicate that ‘is}mah carries two meanings: to prevent or to protect (man‘) and to be steadfast (imsa>k and mula>zamah). Therefore, ‘is}mah has the same meaning as taqwa>, h}ifz}, and isti‘a>dzah. The association of ‘is}mah as a theological concept in the doctrine of prophethood, as commonly discoursed by the mufassirs, is the highest achievement. Meanwhile, the use of this term in the Qur'an shows that ‘is}mah is correlated with three other terms, namely rah}mah, fad}l, and huda>, which focus more on the process of achieving ‘is}mah in the theological context. This article concludes that the ‘is}mah of the prophets is the pinnacle of achievement of the human life process which requires vertical and horizontal faith and piety among human beings.